Antioxidant and anticancer activities on HT-29 colon cancer cells of protein isolate extracted from Cordyceps militaris fruiting body using diverse isolation methods - Thirabunyanon, Mongkol; Mungmueang, Natthapong; Daengprok, Wichittra; Ngampeerapong, Chitraporn; Karnjanapratum, Supatra; Benjakul, Soottawat; Panyakom, Sirin; Senphan, Theeraphol; Sriket, Chodsana (My University, 2024)
The present research examines different techniques for isolating proteins from Cordyceps militaris fruiting body powder (COR), namely ammonium sulfate precipitation (ASP), organic solvent precipitation (OSP), and isoelectric precipitation (IEP). ASP yielded the highest protein content (78.90 %), effectively concentrating proteins, while OSP and IEP also produced substantial yields (57.41 % and 69.06 %, respectively). Color analysis revealed differences among isolates, with ASP resulting in a darker hue. ASP and IEP showed higher red and yellow components, respectively. Essential amino acid content was significantly higher in ASP isolate compared to COR, indicating effective amino acid concentration. Thermal analysis revealed different decomposition temperatures and enthalpy values among isolates. OSP displayed the highest phenolic content, while IEP exhibited the highest flavonoid content. Antioxidant assays showed ASP to have the highest DPPH-RSA and ABTS-RSA, while IEP showed the highest FRAP value. ASP demonstrated anticancer activity against HT-29 colon cancer cells inducing cell death apoptosis and inhibiting cell migration, with an IC50 of 360.63 µg/mL, comparable to Paclitaxel. These findings suggest that Cordyceps militaris protein isolate, particularly from ASP, has significant antioxidant and anticancer potential, supporting its potential as a natural alternative to synthetic drugs with fewer side effects.
Keywords: Anticancer; Antioxidant; Cordyceps militaris; Isolation techniques; Protein isolate